KEPENTINGAN INDONESIA MELAKUKAN KERJASAMA PEMBANGUNAN INFRASTRUKTUR DENGAN TIONGKOK PADA MASA PEMERINTAHAN JOKO WIDODO TAHUN 2014 – 2019 - Vrastian Darulingga; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research discusses Indonesia's interests in infrastructure development cooperation in Indonesia with China in 2014 - 2019. Currently Indonesia is a country that is trying to improve the development of its country. One of the developments that Indonesia is intensifying is development in the infrastructure sector. In carrying out this effort, China is a country that is cooperated by Indonesia. This study explains the overview of infrastructure development in Indonesia, the strategic value of China for Indonesia, and the Indonesian government's policy in conducting infrastructure development cooperation with China. The data in this study were obtained through books, journal articles, documents (government output) and websites. Indonesia in conducting infrastructure cooperation with China is due to the dependence factor with China to meet the needs of Indonesia's infrastructure development efforts. This is evidenced by the financial and labor assistance provided by China. Keywords: Cooperation, infrastructure development, dependence, funds